A Miniaturized MEMS Motion Processing System for Nuclear Medicine Imaging Applications - Mojtaba Jafari Tadi; Eero Lehtonen; Jarmp Teuho; Antti Saraste; Mikko Pänkäälä; Mika Teräs; Tero Koivisto (United States, 2025)
Cardiac, respiratory, and patient body motion artifacts degrade the image quality and quantitative accuracy of the nuclear medicine imaging which may lead to incorrect diagnosis, unnecessary treatment and insufficient therapy. We present a new miniaturized system including joint micro electromechanical (MEMS) accelerometer and gyroscope sensors for simultaneous extraction of cardiac and respiratory signals. We employ two tri-axial joint MEMS sensors for selecting an optimal trigger point in a cardiac and respiratory cycle. The 6-axis motion sensing helps to detect candidate features for cardiac and respiratory gating in Positron emission tomography (PET) imaging. The aim of this study was to validate MEMS-derived signals against traditional Real-time Position Management (RPM) and electrocardiography (ECG) measurement systems in 4 healthy volunteers. High agreement and correlation were found between cardiac and respiratory cycle intervals. These promising first results warrant for further investigations.
Computing in Cardiology 2016